Polymorphism in phenobarbital: discovery of a new polymorph and crystal structure of elusive form V. Issue 23 (1st March 2016) - Roy, Saikat; Goud, N. Rajesh; Matzger, Adam J.
Abstract : This report highlights the discovery of new polymorph 'form XV', and the crystal structure of the elusive form V of the anticonvulsant drug phenobarbital. Abstract : This report highlights the discovery of a new polymorph of the anticonvulsant drug phenobarbital (PB) using polymer-induced heteronucleation (PIHn) and unravelling the crystal structure of the elusive form V. Both forms are characterized by structural, thermal and VT-Raman spectroscopy methods to elucidate phase transformation behavior and shed light on stability relationships.